Chandigarh’s Collaborative Modernism: Departing From Le Corbusier Dominated Narratives - MCCRORY, WILLIAM (2021)
This thesis, enabled by the Midlands3Cities doctoral training programme and supported by The University of Nottingham’s Centre for Critical Theory, presents the notion of ‘collaborative modernism’ as an interpretive lens through which to view the architectural history of Chandigarh, India. The primary aim of this project is to disrupt the Le Corbusier dominated framework that has been constructed around the city and presented by both European and Indian scholarship alike. The idea of collaborative modernism is indebted to the research of scholars Chattopadhyay, Hosagrahar and Glover, that critically reflects on Indian modernity. Equally, the concept has been enriched by the active research clusters at The University of Nottingham, such as The Centre for Critical Theory and The Interdisciplinary Modernism Research Network. Chandigarh is typically considered the work of Le Corbusier; however, my research has shown that the city was the result of a collaboration between Le Corbusier, Pierre Jeanneret, Maxwell Fry, Jane Drew and the Indian team. The concept of collaborative modernism emphasises the agency of the Indian team which at the very least included M.N. Sharma, A.R. Prabhawalkar, B.P. Mathur, Piloo Moody, U.E. Chowdhury, N.S. Lamba, Jeet Malhotra, J.S. Dethe and Aditya Prakash. If we accept that modernity is a stage of capitalism that intrinsically requires something that is globalising, there are consequences for artistic responses to this process, such as modernism. Through exploring whether Chandigarh can be viewed as a back and forth Indo-European exchange, the notion of collaborative modernism will suggest a non-geopolitically specific theorisation of modernism as inherently de-centred. However, it is not necessarily the assertion that the architecture produced by the Indian team was aesthetically different from the architecture produced by the European team, especially since the working relations were inherently collaborative. The claim of collaborative modernism in relation to Chandigarh is intended to emphasise the Indian agency in the design of the city, rather than a significant aesthetic contribution. Indeed, in many ways the focus of this thesis is the character of the working relations that facilitated Chandigarh’s creation, rather than its specific aesthetic or architectural qualities. Accordingly, the city of Chandigarh, and the process that led to its creation, provides a case study through which the lost history of the Indian contribution can be excavated, exploring thereby the complexities of collaborative modernism.